2000
DOI: 10.1103/physrevb.61.5358
|View full text |Cite
|
Sign up to set email alerts
|

High-magnetic-field EPR of Cr-based diluted magnetic semiconductors

Abstract: We have studied magnetic interactions in chromium-based diluted magnetic semiconductors by measuring in detail the electron paramagnetic resonance spectrum of Cr 2ϩ over the frequency range between 30 and 210 GHz at high magnetic fields up to 20 T oriented along different crystal axes. At low temperatures, crystals of chromium-alloyed zinc chalcogenides Zn 1Ϫx Cr x ͑S, Se, Te͒ demonstrate complex properties that are neither of Brillouin nor of Van Vleck type. The behavior of these Cr 2ϩ impurities in semimagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 23 publications
1
12
0
2
Order By: Relevance
“…The observed ferromagnetic p−d exchange interactions in zinc chalcogenides recommends them as the material for spintronics as well [2,6,7]. EPR investigations of the chromium in these crystals reveals this dopant in Cr 2+ state [8,9]. In CdTe matrix the chromium was detected in the same state Cr 2+ [8].…”
Section: Introductionmentioning
confidence: 85%
“…The observed ferromagnetic p−d exchange interactions in zinc chalcogenides recommends them as the material for spintronics as well [2,6,7]. EPR investigations of the chromium in these crystals reveals this dopant in Cr 2+ state [8,9]. In CdTe matrix the chromium was detected in the same state Cr 2+ [8].…”
Section: Introductionmentioning
confidence: 85%
“…However, our g-value and the peak-to-peak line width are in contradiction with the reported values of the ESR spectra of Cr 2+ in II-VI compounds. Vallin et al [40] showed that the Cr 2+ ESR spectra in II-VI compounds have peak-to-peak line widths of 500 G at 20 K. Therefore, the expectation is that at room temperature, ESR signal of Cr 2+ will be broader and unable to observed [41]. Additionally, a study of Cr doped GaAs [42] revealed that the Cr 3+ valence state is predominant if the chromium concentration significantly exceeds the concentration of shallow donors in the crystal.…”
Section: Optical Propertiesmentioning
confidence: 94%
“…Хотя тригональный центр обнаружен не был, регистрировались резонансные переходы типа 0 ↔ ±1 иона Cr 2+ . ЭПР-спектроскопия иона Cr 2+ (d 4 , 5 D, S = 2) в ZnSe хорошо изучена [10][11][12], и идентификация этой примеси не представляет сложности. Во-первых, угловая зависимость обнаруженных переходов (в ста-тье не показана) свидетельствовала о тетрагональной симметрии центров, что соответствует литературным данным.…”
Section: 1unclassified